Imperial Germany and the industrial revolution - Veblen, Thorstein (The University of Michigan Press, 1966)
Contents: The scope of Imperial Germany and the Industrial Revolution extends far beyond the case of Germany. It requires no reading of his equally prophetic and neglected "Opportunity of Japan" written at the same time to realize that Japan is included. The western democracies also come in for attention. The longest chapter in the book is entitled "The Case of England," and the nine-page supplementary note, tucked away in the back of the work, dealing with American captains of finance should lead to a rereading of the main text as "The Case of American."